Investigation of Light Absorption in a ZnS Quantum Dot - Hojjatollah K. Salehani; Maedeh Zakeri (Journal of Spectroscopy)
The light absorption of a ZnS quantum dot with a parabolic confinement potential is studied in this paper in the presence of magnetic field perpendicular to dot plane. The Schrodinger equation of a single electron is solved numerically, and energy spectra and wave functions are obtained. Then, the optical absorption coefficients in transition from ground state to different excited states are calculated. The effects the magnetic field and quantum dot width on the optical absorption are investigated. It is found that the optical absorption coefficient has a blue shift by increasing of magnetic field or confinement strength of quantum dot.